History as Trash: Reading Berlin 2000 - Peter Fritzsche (Studies in 20th & 21st Century Literature, 2004)
The expectation that Berlin, at the cusp of the twenty-first century, should produce "big-city" novels that, like Döblin's Berlin Alexanderplatz in its own time, would catch the encounters, juxtapositions, and historical layerings of the newly reunified capital is perhaps unfair, and certainly a high bar, but it reflects widespread interest in literary representations of this brazenly, even insolently transformed city...
Keywords: twenty-first century; novel; Berlin; big city; Döblin; Berlin Alexanderplatz; reunified capital; reunification; capital city